2018
DOI: 10.1016/j.fishres.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The fishing and illegal trade of the angelshark: DNA barcoding against misleading identifications

Abstract: Morphological identification in the field can be extremely difficult considering fragmentation of species for trade or high similarity between congeneric species. In this context, the shark group belonging to the genus Squatina is composed of three species distributed in the southern part of the western Atlantic. These three species are classified in the IUCN Red List as endangered, and they are currently protected under Brazilian law, which prohibits fishing and trade. Molecular genetic tools are now used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…DNA barcoding has been a promising tool for the identification of species being trade (Staffen et al 2017;Bunholi et al 2018;Feitosa et al 2018). However, the methodology, besides being expensive, requires very specific and contaminationfree protocols which is often difficult to perform in the field.…”
Section: Discussionmentioning
confidence: 99%
“…DNA barcoding has been a promising tool for the identification of species being trade (Staffen et al 2017;Bunholi et al 2018;Feitosa et al 2018). However, the methodology, besides being expensive, requires very specific and contaminationfree protocols which is often difficult to perform in the field.…”
Section: Discussionmentioning
confidence: 99%
“…This unsustainable fisheries situation is likely to stay unchanged or even escalate as unrestricted fishing continues without proper regulation, increasing the imminent risk of extinction for these species [69,70,72]. Although Brazilian law prohibits the capture, commercialization, and trade of many elasmobranch species, they are still illegally captured, landed, and traded [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several studies in Brazil have developed and implemented molecular markers to identified elasmobranchs [25,26,89,90]. However, overall, a few studies have been focused on batoids [28,77,91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has many advantages including life stage, product and species identification, and even system level phylogeographic resolution, with very few disadvantages [e.g. see reviews in [5][6][7][8][9][10][11][12][13][14][15]. The aim of this study is to compile a reference library for the identification of species (e.g.…”
Section: Introductionmentioning
confidence: 99%